Occupational Safety and Health Activities Conducted across Countries in Asia - Jung-Keun Park; Ton T. Khai (Elsevier, 2015)
Three occupational safety and health (OSH) activities, one international and two national workshops, were documented as part of OSH activities conducted under the International Labor Organization/Korea Partnership Program in the year 2011-2012. This study aimed to provide information on what the three OSH activities were implemented and how they contributed to the improvement of OSH in Asian countries. The international workshop was useful for the participants to understand a variety of information on OSH as well as participatory action-oriented training (PAOT) approaches at the regional and global levels. The two national workshops were practical for participants to strengthen their knowledge and skills on the PAOT at the enterprise and national levels. The study shows that the three OSH activities contributed to the understanding of the participants on OSH and PAOT, and that the activities promoted the improvement of OSH across countries in Asia.